2022
DOI: 10.28991/cej-2022-08-10-019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Analytical Study of High-Strength Concrete Containing Natural Zeolite and Additives

Abstract: The study compares the durability of Natural Zeolite with Metakaolin, Silica Fume, and Fly Ash on high-strength concrete. 300 concrete specimens were tested for compressive strength before and after an acid attack, modulus of elasticity, water absorption, and rapid chloride permeability. 5%, 10%, and 15% of the cement were replaced with cementitious elements while maintaining the same quantity of Natural Zeolite. In this investigation, the water-cement ratio was maintained at 0.35. After 28 days, the specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
(39 reference statements)
1
1
0
Order By: Relevance
“…The setting time decreased when the curing temperature increased. Similar results were found in fly ash [45] and metakaolin [13,46] based geopolymers. The high rate of setting was due to the temperature-controlled dissolution of aluminosilicate precursors that were reactive at high temperatures [47].…”
Section: Initial and Final Setting Timesupporting
confidence: 85%
“…The setting time decreased when the curing temperature increased. Similar results were found in fly ash [45] and metakaolin [13,46] based geopolymers. The high rate of setting was due to the temperature-controlled dissolution of aluminosilicate precursors that were reactive at high temperatures [47].…”
Section: Initial and Final Setting Timesupporting
confidence: 85%
“…oxidation of NH 3 to N 2 O, their application to nonelectric plants is limited [4]. In order to develop efficient, nontoxic, economic and wide-temperature-window deNO x catalysts, metal-exchanged zeolite catalysts have received wide attention [5][6][7][8][9][10][11][12]. Jung et al [13] studied the NO x conversion on NH 3 -SCR over the Cu-zeolite catalyst and V 2 O 5 -WO 3 /TiO 2 catalyst, and found that the Cu-zeolite catalyst had a superior activity.…”
mentioning
confidence: 99%